The Application of a Bone Marrow Mesenchymal Stem Cell Membrane in the Vascularization of a Decellularized Tracheal Scaffold. (8th March 2021) - Yao, Zhi-Ye; Feng, Bo-Wen; Liu, Cai-Sheng; Liu, Yu-Mei; Zhou, Hai-Yu; Zhang, Xiao-Hui; Jian, Min-Qiao; Mo, Jian-Ling; Liang, Yi-Jing; Chen, Liang; Liu, Xiao-Qing; Chen, Yan-Ling; et al.
Abstract : Airway stenosis is a common problem in the neonatal intensive care unit (NICU) and pediatric intensive care unit (PICU). A tissue-engineered trachea is a new therapeutic method and a research hotspot. Successful vascularization is the key to the application of a tissue-engineered trachea. However, successful vascularization studies lack a complete description. In this study, it was assumed that rabbit bone marrow mesenchymal stem cells were obtained and induced by ascorbic acid to detect the tissue structure, ultrastructure, and gene expression of the extracellular matrix. A vascular endothelial cell culture medium was added in vitro to induce the vascularization of the stem cell sheet (SCS), and the immunohistochemistry and gene expression of vascular endothelial cell markers were detected. At the same time, vascular growth-related factors were added and detected during SCS construction. After the SCS and decellularized tracheal (DT) were constructed, a tetrandrine allograft was performed to observe its vascularization potential. We established the architecture and identified rabbit bone marrow mesenchymal stem cell membranes by 14 days of ascorbic acid, studied the role of a vascularized membrane in inducing bone marrow mesenchymal stem cells by in vitro ascorbic acid, and assessed the role of combining the stem cell membranes and noncellular tracheal scaffolds in vivo . Fourteen experiments confirmed that cell membranes promote angiogenesis at gene level. The results of 21-day in vitro experiments showed that the composite tissue-engineered trachea had strong angiogenesis. In vivo experiments show that a composite tissue-engineered trachea has strong potential for angiogenesis. It promotes the understanding of diseases of airway stenosis and tissue-engineered tracheal regeneration in newborns and small infants.